Assessing food security through cooking and food literacy among students enrolled in a basic food science lab at Appalachian State University. Issue 1 (2nd January 2023) - Morgan, Maggie; Arrowood, John; Farris, Alisha; Griffin, Jamie
Abstract: A dual relationship between food insecurity and inadequate food literacy among college students may be attributed to limited food literacy, availability and ability to prepare healthful foods. Experiences that increase food literacy can improve diet quality and reduce food insecurity. Research was conducted through a food literacy-based curriculum developed using Social Cognitive Theory and Experiential Learning Theory. Food literacy outcomes and food security level were measured pre- and post-term through a Qualtrics-based survey. Analyses included Wilcoxon Signed Rank test and McNemar test. Analysis was completed on participants who completed both the pre and post surveys (n = 39). Over 30% of participants identified as food insecure. Results showed an increase in food literacy-based behaviors, self-efficacy and confidence (p<.05) in several measurements. Food security did not significantly improve; however, a positive trend toward food secure habits was observed. Food literacy-based self-efficacy and behaviors improved, which increases the potential for engagement and adaptation of related behaviors. Improvements observed may provide positive coping skills to reduce food insecurity. Incorporating a Basic Foods Lab into the General Education, Wellness Literacy curriculum can increase food literacy skills that may translate into reduced food insecurity.